Adult Ube3a Gene Reinstatement Restores the Electrophysiological Deficits of Prefrontal Cortex Layer 5 Neurons in a Mouse Model of Angelman Syndrome - Rotaru, Diana C. (J Neurosci, 2018)
E3 ubiquitin ligase (UBE3A) levels in the brain need to be tightly regulated, as loss of functional UBE3A protein is responsible for the severe neurodevelopmental disorder Angelman syndrome (AS), whereas increased activity of UBE3A is associated with nonsyndromic autism. Given the role of mPFC in neurodevelopmental disorders including autism, we aimed to identify the functional changes resulting from loss of UBE3A in infralimbic and prelimbic mPFC areas in a mouse model of AS. Whole-cell recordings from layer 5 mPFC pyramidal neurons obtained in brain slices from adult mice of both sexes revealed that loss of UBE3A results in a strong decrease of spontaneous inhibitory transmission and increase of spontaneous excitatory transmission potentially leading to a marked excitation/inhibition imbalance. Additionally, we found that loss of UBE3A led to decreased excitability and increased threshold for action potential of layer 5 fast spiking interneurons without significantly affecting the excitability of pyramidal neurons. Because we previously showed that AS mouse behavioral phenotypes are reversible upon Ube3a gene reactivation during a restricted period of early postnatal development, we investigated whether Ube3a gene reactivation in a fully mature brain could reverse any of the identified physiological deficits. In contrast to our previously reported behavioral findings, restoring UBE3A levels in adult animals fully rescued all the identified physiological deficits of mPFC neurons. Moreover, the kinetics of reversing these synaptic deficits closely followed the reinstatement of UBE3A protein level. Together, these findings show a striking dissociation between the rescue of behavioral and physiological deficits. SIGNIFICANCE STATEMENT Here we describe significant physiological deficits in the mPFC of an Angelman syndrome mouse model. We found a marked change in excitatory/inhibitory balance, as well as decreased excitability of fast spiking interneurons. A promising treatment strategy for Angelman syndrome is aimed at restoring UBE3A expression by activating the paternal UBE3A gene. Here we find that the physiological changes in the mPFC are fully reversible upon gene reactivation, even when the brain is fully mature. This indicates that there is no critical developmental window for reversing the identified physiological deficits in mPFC.